The functional treatment of the diaphyseal tibial fractures using plaster cast or external fixator - Litvishko, Valeriy; Popsuishapka, Olexii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
The article is prepared for practical traumatologists. Three main conditions required for the natural process of bone healing with the forming of periosteal bone regenerate are identified and substantiated by the authors. They are following: the presence of intact area with periosteum and muscle that were peeled off the fragments; the forming of fibrin-blood clot near the fragments; the presence of internal intention of fibrin-cell blastema on the stage of proliferation and differentiation of mesenchyme cells. These conditions should be taken into consideration while choosing the methods of reduction of tibia fragments, method of their fixation and regimen of functional activity of injured extremity. Moreover, before choosing the fixation method the grade of fragments fixity in periosteum-muscle envelope should be analyzed. The author proposed the classification of fixity, based on the severity of initial displacement according to radiographic findings: I grade — initial displacement of tibia fragments does not exceed 1/3 of its cross-section; II grade - initial displacement of fragments exceeds 1/3 of its cross-section, but does not exceed the bounds of cross-section, fibula is damaged approximately on the same level, periosteum-muscle envelope is damaged on ½ approximately; III grade – displacement of tibia and fibula exceed their cross-section with shortening, severe damage of periosteum and muscles. The techniques of functional treatment of acute fractures using plaster bandage and original external fixator are described in details.